Device for Reduction Sparking of Slip Ring of Turbo Generator (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Most modern power plants generating electric power equipped with synchronous generators. The correct operation of energy economy depends on reliability of such electrical machines. In this article issue of increasing reliability of turbo generator by increasing reliability of its brush contact unit is considered. Description of brush contact unit and its possible damages is given. Equivalent electrical circuit of contact layer of brush contact unit is performed. The equations are formed and the dynamical simulation model consisting of electric source and two brush contact units is created. With help of this model alternative method of improving parameters of brush contact unit and increasing reliability of turbo generator at once is calculated and shown. The implementation of the proposed method of increasing the turbo generator brush contact units reliability can have different technical performance, but the principle laid down in the method remains the same.